EFEKTIVITAS PENDEKATAN RATIONAL EMOTIVE BEHAVIOUR THERAPY UNTUK MENGURANGI KECANDUAN GAME ONLINE PADA ANAK SEKOLAH DASAR - Fitriatun Solikhah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
This study aims to determine the effectiveness of the Rational Emotive Behavior Therapy (REBT) approach to reduce behavior towards children who are addicted to online games. The subjects in this study were 12 students who were members of the experimental group. The 12 students consisted of 2 children in class IV, 2 children in class V and 2 children in class VI, which were divided into 2 groups, namely a group in the medium category playing online games consisting of 6 students and a group in the category of online game addiction consisting of 6 student. Characteristics of the subjects include: (1) Individuals who are 10 years to 13 years old are students in grades IV, V and VI SD N Jumeneng, (2) students who have grades 4 and 5 from the subject matter questionnaire, (3) are willing to become respondents or subjects this research. The experimental group was treated using the Rational Emotive Behavior Therapy approach for 3 meetings and each meeting of 120 minutes was divided into 3 sessions. The design used is one-group pretest-posttest design. Data collection in this study was carried out using a scale of online game addiction compiled by researchers. The data analysis method used is nonparametric statistics using the Wilcoxon Signed Ranks technique to test the different scores of the two paired samples, the pre-test and post-test data in the experimental group. Wilcoxon Signed Ranks results show that the Rational Emotive Behavior Therapy approach is effective for reducing online game addiction. Both have the same Z and P values, namely z = -2.201 and p = 0.028.